2001
DOI: 10.1152/physiolgenomics.00074.2001
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of acute spinal cord injury reveals spreading inflammatory signals and neuron loss

Abstract: We have completed the first large-scale gene expression study of acute spinal cord injury (SCI) in rat. Oligonucleotide microarrays containing 1,200 gene-specific probes were used to quantify mRNA levels, relative to uninjured controls, in spinal cords injured using a standard contusion model. Our results revealed a marked loss of neuron-specific mRNAs at the injury site. The surviving cells showed a characteristic inflammatory response that started at the injury site and spread to the distal cord. Changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
113
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 53 publications
10
113
0
Order By: Relevance
“…Furthermore Benn et al (77) have discovered that Hsp27 is up-regulated and phosphorylated after nerve injury, and these process are required for neuronal survival. Our present results are consistent with previous reports (24) where it is stated that the amount of Hsp27 increases in the spinal cords of SCI rats ( Fig. 3 and Table II).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore Benn et al (77) have discovered that Hsp27 is up-regulated and phosphorylated after nerve injury, and these process are required for neuronal survival. Our present results are consistent with previous reports (24) where it is stated that the amount of Hsp27 increases in the spinal cords of SCI rats ( Fig. 3 and Table II).…”
Section: Discussionsupporting
confidence: 94%
“…Recently microarray experiments have further demonstrated that Rab3A is decreased 6.8-fold after SCI (24). Furthermore we found that a substantial amount of Rab-GDI can be detected using 2D PAGE analysis in the SCI rats but not in the shams at 24 h after operation.…”
Section: Discussionsupporting
confidence: 48%
“…Previous reports have suggested that p53 (Saito et al, 2000) and p53-dependent signaling (Carmel et al, 2001;Di Giovanni et al, 2003;Byrnes et al, 2006) are activated in both neuronal and glial cells following spinal cord injury (SCI). In addition, we previously found that p53-dependent target genes, including DNA damage, cell cycle, and axonal plasticityrelated molecules are triggered mainly between 1 and 7 d following injury (Di Giovanni et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 99%
“…spinal cord, such as phosphodiesterase 4, nestin, glia-derived neurite promoting factor and growth associated protein 43, were found to increase significantly in a higher level and earlier stage in the distal segment than in the injury site (Carmel et al, 2001;Grossman et al, 2001). T11 section is much closer to the injured site, so regeneration response here should occur later than L2 section.…”
Section: Discussionmentioning
confidence: 92%
“…It is well-known that changes in gene expression in the neurons distal to the injury site could reflect not only the regeneration response but also inflammatory and neuroprotective responses by diffusible signals from the injury site or by loss of synaptic input. In recent years, many investigators have observed the characteristic inflammatory response that emerged robustly at the injury site and spread to the distal cord in a lower level (Carmel et al, 2001;Aimone et al, 2004;De Biase et al, 2005). L2 section is farther from the transected section (between T9 and T10) than the T11 one.…”
Section: Discussionmentioning
confidence: 99%